2020
DOI: 10.1042/bcj20200429
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure and the glutathione cycle: an integrated view

Abstract: Heart failure results from the heart's inability to carryout ventricular contraction and relaxation, and has now become a worldwide problem. During the onset of heart failure, several signatures are observed in cardiomyocytes that includes fetal reprogramming of gene expression where adult genes are repressed and fetal genes turned on, endoplasmic reticulum stress and oxidative stress. In this short review and analysis, we examine these different phenomenon from the viewpoint of the glutathione cycle and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Cardiovascular diseases, as occlusion of the coronary arteries, hypertensive heart diseases and strokes, arterial hypertension, myocardial infarction, cerebrovascular disease, heart failure, rheumatic heart disease, congenital heart disease and cardiomyopathies generate thousands of patients with a high mortality and morbidity rates worldwide [ 1 , 2 , 3 , 4 ]. The appearance of these diseases increases with the aging of the population [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases, as occlusion of the coronary arteries, hypertensive heart diseases and strokes, arterial hypertension, myocardial infarction, cerebrovascular disease, heart failure, rheumatic heart disease, congenital heart disease and cardiomyopathies generate thousands of patients with a high mortality and morbidity rates worldwide [ 1 , 2 , 3 , 4 ]. The appearance of these diseases increases with the aging of the population [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a component of the unfolded protein response (UPR) pathway, Chac1 is known to be a candidate gene for the glutathione-metabolism-signaling pathway, which accelerates glutathione degradation. Considering that glutathione is a crucial intracellular antioxidant, several studies showed that the dysregulation of Chac1 alters intracellular glutathione expression and is associated with various diseases, such as cancer [ 33 ] and heart failure [ 34 ]. Meanwhile, the silencing of Chac1 has recently been found to ameliorate heat stress (HS)-induced intestinal porcine epithelial cell apoptosis due to the upregulation of glutathione, thereby relieving HS-related intestine impairment [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our previous finding that Met-sulfoxide and 5-oxoproline declined during the aggravation of IL1-β-induced HGF inflammation by TiO 2 nanoparticles ( Supplementary Figure S2A,B , cited from [ 15 ]). Since Met-sulfoxide [ 23 , 24 , 25 ] and 5-oxoproline [ 26 , 27 , 28 ] are well-known markers reflecting oxidative stress, SE might have induced the cells to fight against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%